Mapping Management of Innovation and Leadership in the Sustainability of an Organization; Bibliometric Analysis 2020-2022 - Zudi Rahmawan; Wulandari Destri; Parjiyati; Rika Wulansari; Rr. Tisie Yuhara; Ariff Muhamed (SMARTINDO, 2023)
Purpose - ArticleThis paper presents and discusses the impact of an innovation implemented by leadership on the sustainability of an organization which is taken from mapping through biblometric analysis. In order to compete with other organizations, organizations must have innovation and be innovative in looking for new ideas or breakthroughs. In fact, there have been many studies related to management innovation. But here we are interested in examining how much researchers who conduct innovation management research directly related to leadership use bibliometric analysis through VOSViewer. Design/methodology/approach - We use a bibliometric method and review related to Innovation and Leadership management. We obtained the data source for the bibliometrics through the Scopus database. Findings and Discussion – The results of research with mapping using the keyword